2006
DOI: 10.1002/eji.200526175
|View full text |Cite
|
Sign up to set email alerts
|

Solid tumors “melt” from the inside after successful CD8 T cell attack

Abstract: Adoptive transfer of tumor-specific T cells represents a promising approach for cancer immunotherapy. Here, we visualized the anti-tumor response of CD8 T cells from P14 TCR-transgenic mice specific for the model antigen GP33 by immunohistology. P14 T cells, adoptively transferred into tumor-bearing hosts, induced regression of established 3LL-A9 GP33 and MCA102 GP33 tumors that express GP33 as a tumor-associated model antigen. Strikingly, the visible effects of P14 T cell attack, such as the destruction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 47 publications
3
26
0
Order By: Relevance
“…Blohm et al 54 visualized adoptive CD8 þ T-cell-mediated tumor destruction and found that tumors 'melt' from the inside were derived from destruction of tumor vasculature and accumulation of granulocytes. The enhancement of in vivo therapeutic effect of the engineered T TNF cells observed in this study may not be due to its upregulated expression of perforin, but may be associated with its enhanced secretion of the transgenecoded human TNF-a as well as its elongated survival in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Blohm et al 54 visualized adoptive CD8 þ T-cell-mediated tumor destruction and found that tumors 'melt' from the inside were derived from destruction of tumor vasculature and accumulation of granulocytes. The enhancement of in vivo therapeutic effect of the engineered T TNF cells observed in this study may not be due to its upregulated expression of perforin, but may be associated with its enhanced secretion of the transgenecoded human TNF-a as well as its elongated survival in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In some models, the ability of CTLs to kill (at least some) tumor or stromal cells appeared essential for tumor elimination (5)(6)(7)(8)(9). Other studies have noted a critical role for CD8 + T cell-derived IFN-γ (10)(11)(12)(13)(14)(15) and the recruitment of inflammatory cells. In addition, some CTLs act primarily by promoting the expansion of other anti-tumor T cell clones (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a multitude of experimental studies has provided strong support in favor of the immune surveillance hypothesis, and it is now generally accepted that the immune system is capable of identifying and eradicating tumor cells (1,2). In addition, comprehensive research in the field has revealed that CTLs play a major role in tumor rejection, and the number of tumorinfiltrating CD8 T cells has often been found to correlate with a good prognosis (3)(4)(5)(6)(7)(8). As a result, many groups have tried to elicit strong antitumor CD8 T cell responses using a variety of vaccination strategies, and many murine model studies have provided promising results.…”
mentioning
confidence: 99%